2013
DOI: 10.1111/j.1600-048x.2013.05871.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of songbird migration: individual consistency within and between seasons

Abstract: The timing of migration is generally considered of utmost importance for reproduction and survival, and timing is furthermore considered to be under strong genetic control. The individual timing of migration is presumably a result of a combination of genetic, phenotypic and environmental factors as well as some degree of randomness. However, potential differences in consistency of timing between spring and autumn and between migration strategies are not well studied. Using long‐term Danish ringing data, we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In terms of temporal aspects of migration, it has generally been reported significant repeatability of timing of migration in a wide variety of bird species (Lourenco et al 2011, Stanley et al 2012, Conklin et al 2013, Thorup et al 2013, Gill et al 2014, Lopez-Lopez et al 2014). These patterns have been interpreted as reflecting strong endogenous control of timing of migration in long-distance migrants (in particular for spring migration; Berthold 1996, Stanley et al 2012, Both et al 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of temporal aspects of migration, it has generally been reported significant repeatability of timing of migration in a wide variety of bird species (Lourenco et al 2011, Stanley et al 2012, Conklin et al 2013, Thorup et al 2013, Gill et al 2014, Lopez-Lopez et al 2014). These patterns have been interpreted as reflecting strong endogenous control of timing of migration in long-distance migrants (in particular for spring migration; Berthold 1996, Stanley et al 2012, Both et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The general pattern that has emerged from recent repeatability analyses of tracking data as well as ringing–resighting studies of the same individuals in different years, is that migratory birds show relatively high individual consistency in timing of migration but relatively low individual consistency in migration routes (Battley , Lourenco et al , Vardanis et al , Stanley et al , Conklin et al , Thorup et al , Gill et al , Lopez‐Lopez et al , Sergio et al ). For stopover site studies the results of ringing – resighting data are mixed, with songbirds showing low spatial consistency between years (Catry et al , but see Merom et al ), whereas many shorebirds show medium to high spatial consistency (Smith and Houghton , Gunnarsson et al , Conklin et al ).…”
mentioning
confidence: 99%
“…is 0.37 (n  = 759). Nevertheless, Thorup et al 12. found that migratory passerines of northern Europe had significant repeatability ( r  = 0.2–0.5) of spring or autumn migration timing.…”
Section: Discussionmentioning
confidence: 99%
“…Repeatability estimates the upper limit of the heritability of phenotypic traits as the proportion of inter-individual or intra-class variance of phenotypic traits in total phenotypic variance1011. If between-individual differences reflect inter-individual genetic differences, high repeatability may suggest genetic control, providing insight into the microevolution of avian migration timing312. Estimation of avian migration timing repeatability has been hindered by lack of accurate, repeated observations of migration timings until recent advances in global positioning system (GPS) tracking technology.…”
mentioning
confidence: 99%
“…Data from May, June and July were used for the breeding ranges, and from November, December and January for the wintering ranges. Exact arrival and leaving dates are not available for many migrants, but the migratory species in our dataset are highly likely to be in their breeding or wintering ranges during these months [34][35][36][37][38]. We also calculated a single value for temperature and precipitation for migrants by combining both sets of seasonal data.…”
Section: (B) Characterizing the Environments Occupied By Species (I) mentioning
confidence: 99%